How are my Students going? A Tool to Analyse Students' Interactions on Capstone Courses - Lima, Márcia; Fontão, Awdren; Fernandes, David; Conte, Tayana; Gadelha, Bruno (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2019)
Computing-related undergraduate students are encouraged to participate in Project-based Learning (PBL) courses through capstone courses in order to bridge the gap between software engineering (SE) educational and industrial worlds. In these courses, students improve their skills on industrial tools and processes and engage in real-world projects. One of the challenges of this kind of courses is how to monitor students' progress. In this work, we propose a software tool based on statistical analysis and data-mining algorithms to investigate the usefulness of students' communication logs to support professors' pedagogical activities during a capstone course involving three different SE disciplines. Our results indicate the feasibility of using textual content and metadata content extracted from Slack logs to identify opportunities for the professor's intervention. A quantitative analysis reveals an average precision of 81% at identifying the top-5 relevant sentences registered in the log.